Good practices implemented in the framework of the COVID 19 pandemic to guarantee the right to identity of newborns in Peru - Fernández Velásquez, Eliana Lisette (2022)
Before March 16, 2020, the National Register of Identification and Civil Status – RENIEC, as governing body in charge of the national registry of identification and civil status in Peru, it has been working as usual. One of its main functions is the inscription of births. However, with the arising of the COVID 19 pandemic and all the restrictions that this situation provoked, there were a series of problems for the registration of newborns. Therefore, RENIEC as several bodies of the State directly related to this role, looked for practical solutions to guarantee the right to identity of newborns. The given solutions were based on good practices implemented by these institutions previously to COVID 19 – such as the online Certificate of live birth – and others that arose because of the pandemic (suspension of the terms, use of certificate of live birth to identify the newborn, biofacial DNI (National Identity Document), which allowed, during this health emergency, to continue with the registration of births and to obtain the national identity document of the newborn swiftly, effectively and without leaving home. The situation was different in other countries of the region where the right to identity of newborns was affected because they did not have the adequate mechanisms to make the registration. Therefore, the good practices implemented by the different Peruvian institutions directly related to the inscription of births have been successful because they have guaranteed the right to identity of newborns, but above all they have been implemented considering the human being and its dignity as center and end of society and State, framing its actions within the bioethics and person-based current.